(untitled) (International Journal of Biomedical Research, 2014)
Background : Study of epidermal ridges and their configuration on the tips of fingers, palm and soles is called as dermatoglyphic study or Dermatoglyphics, is a typical clue for personal identification. If any influences which are acting either in form of factor or drugs which act prior to particular intrauterine period when finger print pattern is developing, it is bound to cause changes in these patterns like in cardiovascular system of foetus in form of congenital cardiac diseases. Material and Method : Various dermatoglyphic parameters like finger print pattern, atd angle, absolute ridge count and ab, bc ,cd, and ad ridge counts were observed in 150 cases of congenital cardiac disease, comprising of 72 cases of Ventricular Septal Defects (VSD), 60 cases of Atrial Septal Defects (ASD), 9 cases of Co-arctation of Aorta (COA) and 9 cases of Tetralogy of Fallots (TOF). Same dermatoglyphic parameters were also studied in 300 controls and statistical comparison of cases and controls was done. Result and conclusion : It was observed that the congenital cardiac disease cases exhibited preponderance of whorls (55.8%) with decrease in loop pattern (36.2%) as compared to those of controls and the difference was highly significant (p 0.001). The difference in the mean total finger ridge count (TFRC) of the controls and of the cases of Congenital Cardiac Diseases (CCD) was found to be highly significant (p 0.001), while the mean atd angle in the cases of Congenital Cardiac Disease (CCD) was widen up and was statistically significant too. The mean ab, the mean bc ridge, the mean cd ridge and the mean ad ridge counts were also higher in the various type of CCD as compared to that controls and on statistical comparison, the difference was found to be highly significant.